The age of innocence - Wharton, Edith; Day-Lewis, Daniel; Pfieffer, Michelle; Ryder, Winona; Cocks, Jay; Scorsese, Martin ([Place of production not identified] Columbia Pictures, 1993)
"A tale of nineteenth-century New York high society in which a young lawyer falls in love with a woman separated from her husband, while he is engaged to the woman's cousin."--https://www.imdb.com/title/tt0106226
Produced by Barbara De Fina; music by Elmer Bernstein; cinematography by Michael Ballhaus.
Daniel Day-Lewis, Michelle Pfieffer, Winona Ryder.
DVD
In English.
Keywords: Drama; Romance